6d-1-3d=55+2d

Simple and best practice solution for 6d-1-3d=55+2d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6d-1-3d=55+2d equation:


6d - 1 - 3d = 55 + 2d

We simplify the equation to the form, which is simple to understand
6d-1-3d=55+2d

We move all terms containing d to the left and all other terms to the right.
+6d-3d-2d=+55+1

We simplify left and right side of the equation.
+1d=+56

We divide both sides of the equation by 1 to get d.
d=56

See similar equations:

| 11(x+4)-3x=4(2x+2)-10 | | 30=t-12 | | (4x^2+34x+40)/(x+7) | | 3d+4-(-2d)=5d+33 | | -14x+3(x-4)+7x=5x-12 | | 3d-4+(-2d)=5d+33 | | 2x+2(x-5)=3x-5 | | (3x/4)-(2x/5)=1 | | y-5=7/8x-7/8-2 | | 15x-8x=1 | | -2x-2=20-2 | | 12. 3(4x-1)=21 | | 5x+8=4-(7x-5) | | 5x+8=4-bracket(7x-5) | | 2x+6=7-(6x-4) | | 2(x+3)+2=10 | | x+3=x+7 | | 45-15=-15m | | 9y-7-5y=5y-6 | | 5*2-8=39x | | -1/1(x+1)=-4 | | 1/2(x+2)=1 | | -1/2x-5=-6 | | 4/x=7/4x+3 | | y+1=5/6(x-1) | | 65-4x=5x+15 | | y-1=5/6(x-1) | | 5-8x=77-36x | | 8x+12=27 | | y-5=3(x-6) | | 9x+y=72 | | (11x)-5=180 |

Equations solver categories